2017
DOI: 10.3386/w24113
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Peer Genotypes and Behavior on Smoking Outcomes: Evidence from Add Health

Abstract: At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w24113.ack NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Similar work finds that state-level mean PGS for education predicts attainment net the individual's score in HRS data (Domingue et al 2018b). Other recent research deploys quasiexperimental analytic strategies to draw a plausibly causal through-line between the genetic propensity to smoke among school alters, peer smoking behavior, and ego smoking behavior (Sotoudeh, Conley, and Harris 2017). In a similar line of work, researchers have also examined the influence of the parents' genomes on educational outcomes net the children's own endowment, whereby alleles that are not transmitted intergenerationally nevertheless have a putative effect on outcomes through environmental channels, or "genetic nurturance" (Belsky et al 2018;Kong et al 2018;Liu 2018).…”
Section: Spatial Sorting Neighborhood Effects and Attainments And Mechanisms Of Stratificationmentioning
confidence: 85%
“…Similar work finds that state-level mean PGS for education predicts attainment net the individual's score in HRS data (Domingue et al 2018b). Other recent research deploys quasiexperimental analytic strategies to draw a plausibly causal through-line between the genetic propensity to smoke among school alters, peer smoking behavior, and ego smoking behavior (Sotoudeh, Conley, and Harris 2017). In a similar line of work, researchers have also examined the influence of the parents' genomes on educational outcomes net the children's own endowment, whereby alleles that are not transmitted intergenerationally nevertheless have a putative effect on outcomes through environmental channels, or "genetic nurturance" (Belsky et al 2018;Kong et al 2018;Liu 2018).…”
Section: Spatial Sorting Neighborhood Effects and Attainments And Mechanisms Of Stratificationmentioning
confidence: 85%
“…The idea of social genetic effects originated in evolutionary theory (Moore, Brodie, and Wolf 1997;Wolf et al 1998), and social genetic effects have been observed in animal populations (Petfield et al 2005;Bergsma et al 2008;Canario, Lundeheim, and Bijma 2017;Baud et al 2018). Social science is now beginning to study such effects in human populations; examples include among social peers (Sotoudeh, Conley, and Harris 2017;Domingue et al 2018), sibling pairs (Cawley et al 2017;Kong et al 2018), and parents and their children (Bates et al 2018;Kong et al 2018;Wertz et al 2018). The existence of within-family social genetic effects complicates attempts to derive causal estimates from GWAS.…”
Section: B the Problem Of Confoundingmentioning
confidence: 99%
“…Finally, a very recent set of studies uses peers' genetic information to address the reflection problem. Sotoudeh et al (2017) use peers' distribution of polygenic scores associated with tobacco use to instrument for peer smoking. A polygenic score is a weighted average or composite score that takes into account information across an individual's entire genome to measure his/her genetic predisposition or risk for a particular outcome.…”
Section: A) Identification Using Instrumental Variables: Peers' Family Background Exogenous Shocks and Genetic Phenotypesmentioning
confidence: 99%
“…Siblings' genes, however, could affect the food that is prepared at home, the promotion of exercise in the household, or other traits of the individual different from BMI, and could thus have an influence on the individual's BMI through other channels. Sotoudeh et al (2017) take this argument further and question the adequacy of using siblings' genes to explain social interactions at the family level. Because siblings' genes will be correlated with parental genes, they may be a proxy for environmental common shocks that result from parents' behavior (food or fitness related) and that influence siblings' weight.…”
Section: C) Reduced Form Models That Combine Contextual and Endogenous Effectsmentioning
confidence: 99%